RZWQM2 Simulated Irrigation Strategies to Mitigate Climate Change Impacts on Cotton Production in Hyper–Arid Areas - Xiaoping Chen; Haibo Dong; Shaoyuan Feng; Dongwei Gui; Liwang Ma; Kelly R. Thorp; Hao Wu; Bo Liu; Zhiming Qi (Agronomy, 2023)
Improving cotton (Gossypium hirsutum L.) yield and water use efficiency (WUE) under future climate scenarios by optimizing irrigation regimes is crucial in hyper-arid areas. Assuming a current baseline atmospheric carbon dioxide concentration (<semantics><mfenced open="[" close="]" separators="|">CO2</mfenced>atm</semantics>) of 380 ppm (baseline, BL0/380), the Root Zone Water Quality Model (RZWQM2) was used to evaluate the effects of four climate change scenarios—S1.5/380 (<semantics>∆<msubsup>Tair°</msubsup>=1.5 °C,∆<mfenced open="[" close="]" separators="|">CO2</mfenced>atm=0</semantics>), S2.0/380 (<semantics>∆<msubsup>Tair°</msubsup>=2.0 °C,∆<mfenced open="[" close="]" separators="|">CO2</mfenced>atm=0</semantics>), S1.5/490 (<semantics>∆<msubsup>Tair°</msubsup>=1.5 °C,∆<mfenced open="[" close="]" separators="|">CO2</mfenced>atm=+110 ppm</semantics>) and S2.0/650 (<semantics>∆<msubsup>Tair°</msubsup>=2.0 °C,∆<mfenced open="[" close="]" separators="|">CO2</mfenced>atm=+270 ppm</semantics>) on soil water content (θ), soil temperature (<semantics><msubsup>Tsoil°</msubsup></semantics>), aboveground biomass, cotton yield and WUE under full irrigation. Cotton yield and irrigation water use efficiency (IWUE) under 10 different irrigation management strategies were analysed for economic benefits. Under the S1.5/380 and S2.0/380 scenarios, the average simulated aboveground biomass of cotton (vs. BL0/380) declined by 11% and 16%, whereas under S1.5/490 and S2.0/650 scenarios it increased by 12% and 30%, respectively. The simulated average seed cotton yield (vs. BL0/380) increased by 9.0% and 20.3% under the S1.5/490 and S2.0/650 scenarios, but decreased by 10.5% and 15.3% under the S1.5/380 and S2.0/380 scenarios, respectively. Owing to greater cotton yield and lesser transpiration, a 9.0% and 24.2% increase (vs. BL0/380) in cotton WUE occurred under the S1.5/490 and S2.0/650 scenarios, respectively. The highest net income ($3741 ha−1) and net water yield ($1.14 m−3) of cotton under climate change occurred when irrigated at 650 mm and 500 mm per growing season, respectively. These results suggested that deficit irrigation can be adopted in irrigated cotton fields to address the agricultural water crisis expected under climate change.